Counseling of the Use of Herbal Medicines for Health Care to the Community - Parisa, Nita; Kamaluddin, M. T.; Theodorus; Saleh, Mgs. Irsan; Lusiana, Evi; Tamzil, Nia Savitri; Wicaksono, Bonanza Abi; Nashif, Arkan Abdullah (Indonesian Community Empowerment Journal, 2022)
Herbal medicine is growing quite rapidly, especially in every area that has traditional medicine using natural ingredients that are believed to treat disease. In addition, the use of herbal medicines is believed to have fewer side effects compared to conventional medicine. WHO also recommends the use of traditional and herbal medicines in efforts to maintain health, as well as prevent and treat diseases ranging from mild to chronic diseases. Based on the various problems faced, the purpose of implementing community service is to increase public knowledge and understanding of medicinal plants, independent health screening, and self-medication, and the role of supplements (vitamins and herbs) in health care and disease prevention efforts.